2022
DOI: 10.1111/ijcs.12807
|View full text |Cite
|
Sign up to set email alerts
|

Sense of belonging, international migrants’ spending, and implications for their subjective well‐being

Abstract: A lack of a sense of belonging in the host country has become one of the most common challenges facing international migrants in today's sociopolitical environment.Our two online experiments with 881 international migrant workers in the United States jointly demonstrate that, to cope with their lack of a sense of belonging in the host country, international migrants may spend money suboptimally: more on material purchases but less on experiential and prosocial purchases. More importantly, our studies suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The feelings of relatedness from socialization belong to the third‐level need category of love and belongingness, the feelings of autonomy and competency belong to the fourth‐level need category of esteem, and the feelings of creative entertainment belong to the fifth‐level need category of self‐actualization (Oleson, 2004). Given that satisfaction of needs contributes to the quality of life (Costanza et al, 2007; Hang & Zhong, 2022), we expect that the metaverse consumers whose needs are satisfied would experience increased life satisfaction. Particularly, adopting the application of the mood management theory of Reinecke et al (2012) that the desire for mood management through media is to satisfy intrinsic needs, we hypothesize that social metaverse consumption as mood management (i.e., positive mood enhancement and negative mood alleviation) can positively influence life satisfaction of users.Hypothesis Social metaverse consumption as (a) positive mood enhancement and (b) negative mood alleviation positively influences consumers' life satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The feelings of relatedness from socialization belong to the third‐level need category of love and belongingness, the feelings of autonomy and competency belong to the fourth‐level need category of esteem, and the feelings of creative entertainment belong to the fifth‐level need category of self‐actualization (Oleson, 2004). Given that satisfaction of needs contributes to the quality of life (Costanza et al, 2007; Hang & Zhong, 2022), we expect that the metaverse consumers whose needs are satisfied would experience increased life satisfaction. Particularly, adopting the application of the mood management theory of Reinecke et al (2012) that the desire for mood management through media is to satisfy intrinsic needs, we hypothesize that social metaverse consumption as mood management (i.e., positive mood enhancement and negative mood alleviation) can positively influence life satisfaction of users.Hypothesis Social metaverse consumption as (a) positive mood enhancement and (b) negative mood alleviation positively influences consumers' life satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that satisfaction of needs contributes to the quality of life (Costanza et al, 2007;Hang & Zhong, 2022), we expect that the metaverse consumers whose needs are satisfied would experience increased life satisfaction. Particularly, adopting the application of the mood management theory of Reinecke et al (2012) that the desire for mood management through media is to satisfy intrinsic needs, we hypothesize that social metaverse consumption as mood management (i.e., positive mood enhancement and negative mood alleviation) can positively influence life satisfaction of users.…”
Section: The Effect Of Mood Management On Consumers' Satisfaction Wit...mentioning
confidence: 99%
“…Social exclusion can affect individuals' emotions, cognition, and behavior. It can threaten an individual's existential value and self-identity (Blackhart et al, 2009;Hang & Zhong, 2023). In serious cases, it can induce aggressive driving (Li et al, 2022), antisocial behaviors (Perchtold-Stefan et al, 2022), indirect misbehaviors (Gong et al, 2022), and unethical behaviors (Liu et al, 2023;Tuncel & Kavak, 2022).…”
Section: Social Exclusionmentioning
confidence: 99%
“…Existing research has identified an array of consumer‐level factors that influence demand for counterfeit or inauthentic products across different countries, include individual differences (e.g., Katyal et al, 2022), consumer motives (Le Roux et al, 2019), benign/ malicious envy (Gupta & Lyndem, 2024), moral and economic justifications (Poddar et al, 2012; Siahtiri et al, 2022), cognitive resources (Kim et al, 2012), brand personality perceptions (Bian & Moutinho, 2009), and need for belonging (Hang & Zhong, 2023; Zhang et al, 2023). Consumers, in many cases, are aware of their buying counterfeits through illegal channels for inferior quality at a low price.…”
Section: Literature Background and Conceptual Frameworkmentioning
confidence: 99%